Unresolved issues in custody matters: the position in Malaysia - Abd Malek, Normi (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
There are still many issues which require attention with regard to matters pertaining to custody of children in Malaysia. First and foremost, the meaning of custody is not clearly defined in the two important statutes dealing with custody in Malaysia namely Law Reform (Marriage and Divorce) Act 1976 (LRA) and Guardianship of Infant Act 1961(GIA). This causes confusion in its application. As a result of this unclear definition, the difference between custody and guardianship is also not clear. The Federal Court’s judgment in the case of Amarapathi a/p Periasamy v Muniandy a/l Periasamy, which ruled that LRA and GIA are only applicable to parents of the child, also gives an impact to other relevant and interested parties in custody cases such as grandparents, aunts or foster parents. The law should also stress on parental responsibilities rather than parental rights in order to ensure that the ultimate aim of protecting the interests of the children will always be given special attention. Thus, access to the child should also be viewed as a responsibility on the part of parents rather than merely a right. This paper highlights and discusses the above issues. Suggestions and recommendations, wherever appropriate, are made in order to improve the law.